Fuller Brush Company Moth Proofer - Science History Institute (2018)
Fuller brand insecticide aerosol spray can with white, teal, and red text on teal, brown, red, and white label with moth graphics. Round teal cap.
Keywords: Pesticides; DDT (Insecticide); Insecticides